DAMPAK PEMBANGUNAN JALAN TERHADAP PENDAPATAN FAKTOR PRODUKSI INTRA DAN INTER REGIONAL KBI-KTI - Slamet Muljono; Bonar M. Sinaga; Max Antameng; Arief Daryanto (Jurnal Transportasi, 2010)
The objective of this study is to analyze the impact of road construction on production factor income both forIntra and Inter West-East Region of Indonesia. The model used is named Interregional Social AccountingMatrix West and East Region of Indonesia (IRSAM WEI). Within the IRSAM WEI framework, constructionsector is disaggregated into construction of road infrastructure (including bridge) and others construction.Meanwhile urban and rural household income classification is disaggregated into low, middle, and highincomes. The result shows that the impact of road construction may increase production factor income. BothWI and EI urban areas gain larger benefit of production factor income than rural areas. In addition,interregionally, the WI gain more than the EI.Keywords: road construction, factor production income, interregional social accounting matrix